2003
DOI: 10.1037/0022-3514.84.5.1011
|View full text |Cite
|
Sign up to set email alerts
|

When forgiving enhances psychological well-being: The role of interpersonal commitment.

Abstract: The present research addresses the question of when and why forgiving might enhance psychological well-being. The authors predict that forgiving is associated with enhanced well-being but that this association should be more pronounced in relationships of strong rather than weak commitment. This hypothesis received good support in Studies 1-3. Studies 2 and 3 addressed the issue of why forgiving might be associated with psychological well-being, revealing that this association was reduced after controlling for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
289
1
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 292 publications
(328 citation statements)
references
References 57 publications
(112 reference statements)
24
289
1
14
Order By: Relevance
“…People who are more close or committed to their partner are more likely to make benign attributions regarding the partner's behaviour, which will in turn promote forgiveness (Finkel et al, 2002). Karremans and Aarts (2007) reasoned that over the course of a close and committed relationship, people may ''learn'' that a forgiving response (as compared to a retaliatory response) towards a partner's destructive act often results in relatively positive outcomes (including individual as well as relationship well-being, see below: Karremans, Van Lange, Ouwerkerk, & Kluwer, 2003;Paleari, Regalia, & Fincham, 2005). Such positive outcomes that are associated with the forgiving response may reinforce a person to respond with forgiving rather than retributive tendencies in response to destructive acts of the partner.…”
Section: Priming Effects On Temporary Levels Of Forgivenessmentioning
confidence: 99%
“…People who are more close or committed to their partner are more likely to make benign attributions regarding the partner's behaviour, which will in turn promote forgiveness (Finkel et al, 2002). Karremans and Aarts (2007) reasoned that over the course of a close and committed relationship, people may ''learn'' that a forgiving response (as compared to a retaliatory response) towards a partner's destructive act often results in relatively positive outcomes (including individual as well as relationship well-being, see below: Karremans, Van Lange, Ouwerkerk, & Kluwer, 2003;Paleari, Regalia, & Fincham, 2005). Such positive outcomes that are associated with the forgiving response may reinforce a person to respond with forgiving rather than retributive tendencies in response to destructive acts of the partner.…”
Section: Priming Effects On Temporary Levels Of Forgivenessmentioning
confidence: 99%
“…Ripely and Worthington (2002) also found that forgiveness was positively associated with martial satisfaction. Furthermore, reconciliation-relevant behaviors (e.g., partner forgiveness for cheating) are related to life satisfaction, particularly in the context of extremely committed relationship (Karremans, Van Lange, Ouwerkerk, & Kluwer, 2003). Likewise, Buchard, et al (2003) found that forgiveness is positively associated with life satisfaction.…”
Section: Outcomes Of the Recovery Processmentioning
confidence: 98%
“…Further, Karremans, Van Lange, and Holland (2005) found that the increased prosocial cognitions, feelings, and behaviors that manifest through forgiveness have a spillover effect on more general attitudes -helping individuals who engage in forgiveness to have a prosocial frame of mind and feelings of relatedness toward others. In contrast, victimized employees who do not forgive will experience more psychological tension and discomfort because of conflicting cognitions and feelings (Karremans, Van Lange, Ouwerkerk, & Kluwer, 2003), and they are also more likely to retain feelings of anger, resentment, and anxiety as they ruminate on previous victimization experiences (e.g., Worthington & Scherer, 2004). It seems reasonable to presume that these negative cognitive and emotional states will have a corresponding adverse impact on job-related attitudes, on the employee's ability to cope with workplace demands, and on their desire to remain with their organization.…”
Section: Mediating Role Of Forgiveness When Workgroup Conflict Moderatesmentioning
confidence: 99%